Empirical models of Chinese government bond yields - Tanweer Akram; Shahida Pervin (Levy Economics Institute of Bard College, 2024)
This paper econometrically models the dynamics of long-term Chinese government bond (CGB) yields based on key macroeconomic and financial variables. It deploys autoregressive distributive lag (ARDL) models to examine whether the short-term interest rate has a decisive influence on the long-term CGB yield, after controlling for various macroeconomic and financial variables, such as inflation or core inflation, the growth of industrial production, the percentage change in the stock price index, the exchange rate of the Chinese yuan, and the balance sheet of the People's Bank of China (PBOC). The findings show that the short-term interest rate has an economically and statistically significant effect on the long-term CGB yield of various maturity tenors. John Maynard Keynes claimed that the central bank's policy rate exerts an important influence over long-term government bond yields through the short-term interest rate. The paper's findings evince that Keynes's claim holds for China, implying that the PBOC's actions are a driver of the long-term CGB yield. This means that policymakers in China have considerable leeway in fiscal and monetary operations, government deficit finance, and central government debt management.
Keywords: E43; E50; E58; E60; G10; G12; 330; Chinese Government Bonds; Long-term Interest Rates; Short-term Interest Rates; People's Bank of China; John Maynard Keynes